Pre-sleep protein supplementation does not improve recovery from load carriage in British Army recruits (part 2) - Chapman, Shaun; Roberts, Justin; Roberts, Andrew J.; Ogden, Henry; Izard, Rachel; Smith, Lee; Chichger, Havovi; Struszczak, Lauren; Rawcliffe, Alex J. (Frontiers in Nutrition, 2023)
British Army basic training (BT) is physically demanding with new recruits completing multiple bouts of physical activity each day with limited recovery. Load carriage is one of the most physically demanding BT activities and has been shown to induce acute exercise-induced muscle damage (EIMD) and impair muscle function. Protein supplementation can accelerate muscle recovery by attenuating EIMD and muscle function loss. This study investigated the impact of an additional daily bolus of protein prior to sleep throughout training on acute muscle recovery following a load carriage test in British Army recruits. 99 men and 23 women (mean ± standard deviation [SD]: age: 21.3 ± 3.5 yrs., height: 174.8 ± 8.4 cm, body mass 75.4 ± 12.2 kg) were randomised to dietary control (CON), carbohydrate placebo (PLA), moderate (20g; MOD) or high (60g; HIGH) protein supplementation. Muscle function (maximal jump height), perceived muscle soreness and urinary markers of muscle damage were assessed before (PRE), immediately post (POST), 24-hours post (24h-POST) and 40-hours post (40h-POST) a load carriage test. There was no impact of supplementation on muscle function at POST (p=0.75) or 40h-POST (p=0.989) load carriage but jump height was greater in PLA compared to HIGH at 24h-POST (p=0.037). There was no impact of protein supplementation on muscle soreness POST (p=0.605), 24h-POST (p=0.182) or 40h-POST (p=0.333). All groups had increased concentrations of urinary myoglobin and 3-methylhistidine, but there was no statistical difference between groups at any timepoint (p>0.05). We conclude that pre-sleep protein supplementation does not accelerate acute muscle recovery following load carriage in British Army recruits during basic training. The data suggests that consuming additional energy in the form of CHO or protein was beneficial at attenuating EIMD, although it is acknowledged there were no statistical differences between groups. Although EIMD did occur as indicated by elevated urinary muscle damage markers, it is likely that the load carriage test was not arduous enough to reduce muscle function, limiting the impact of protein supplementation. Practically, protein supplementation above protein intakes of 1.2g⸱kg-1⸱day-1 following load carriage over similar distances (4km) and carrying similar loads (15-20kg) does not appear to be warranted.